Notary's Responsibility for Loss of Minutes of Deed Due To Negligence - Dardiri, Ismail; Hasana, Dahniarti (TABELLIUS: Journal of Law, 2024)
The implication of the Notary's obligation to keep the minutes of the deed, if the minutes of the deed are lost due to his or his employees' carelessness, it can be said that the Notary has not carried out his obligations, and is subject to sanctions ranging from written warnings to dishonorable dismissal. The purpose of this study is to determine and analyze: 1). The Notary's responsibility for the loss of minutes of the deed due to his negligence. 2) Application of Notary Sanctions whose Negligence Resulted in the Loss of Minutes of the Deed and the Obligation to Keep Minutes of the Deed. The approach method in this study is sociological juridical. The data used are primary and secondary data obtained through interviews and literature studies. The technique of collecting legal materials in this study is by using observation techniques, interviews and literature review techniques (document studies) while the data analysis method is carried out using descriptive analytical methods. The results of the research concluded: 1) The role and responsibility of a Notary in resolving the problem of the loss of minutes of a deed due to negligence is in accordance with Article 16 paragraph (1) letter b of the Notary Law, namely making a deed in the form of minutes of a deed and storing it as part of the Notary Protocol. In resolving the loss of minutes of a deed, one of the ways is to compensate the parties, if the parties are harmed by the Notary concerned, while sanctions for Notaries who are negligent in storing the minutes of a deed they have made can be subject to sanctions in the form of verbal warnings, written warnings, temporary dismissal, honorable dismissal and dishonorable dismissal. 2) Legal implications for Notaries who due to their negligence result in the loss of minutes of a deed, namely they can be subject to sanctions, as stated in Article 9 paragraph (1) letter d of the UUJN, namely temporary dismissal from their position as Notaries for violating the obligations and prohibitions of their position. Notaries in carrying out their position must remember that the deed made by or before them is an Authentic Deed. The Authentic Deed is in the form of minutes of the deed which becomes a State Document/Archive and the agreement stated therein becomes law for those who make it. If the Notary in making the deed does not comply with the applicable laws and regulations, in this case it is not in accordance with the UUJN, then the Notary's actions can be qualified as an unlawful act. Unlawful Acts are regulated in Articles 1365 to 1380 of the Civil Code. Article 1365 states that every unlawful act that causes loss to another person causes the person who is wrong to issue the loss to compensate for the loss.